Unsur Menyalahgunakan Wewenang dalam Undang-Undang Pemberantasan Tindak Pidana Korupsi - Revata Vappa Lazuardi; Luthfie Arya Deanova (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The defendant Haris Yasin Limpo, who is the Main Director of the Regional Drinking Water Company (PDAM) of Makassar City, together with Irawan Abadi, committed the crime of corruption by distributing bonuses and company bonuses/services based on Ujung Pandang Level II Regional Regulation Number 6 of 1974 from 2017-2019 should be based on Government Regulation Number 54 of 2017 concerning Regional-Owned Enterprises, the Defendant also paid dual-purpose insurance premiums for the positions of Mayor and Deputy Mayor of Makassar in 2016-2018 even though it is in the Minister of Home Affairs Regulation Number 2 of 2007 concerning Organs and Regional Drinking Water Company personnel who must be included are only Directors and Employees. The imposition of Article 3 of the Corruption Law on the defendant is inappropriate as per Corruption Court Decision Number 59/Pid.Sus-Tpk/2023/PN Mks because the defendant does not fulfill the elements of abusing authority. The panel of judges should apply Article 2 paragraph (1) of the Corruption Law because its elements are more appropriate to the actions committed by the Defendant.